Representasi etnis Tionghoa dalam media: Analisis perbandingan di media berita daring tirto.id, republika.co.id, dan tempo.co - Harsono, Ari; Mazi, Aqila (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Ethnic representation in media is one the most powerful factor in forming people’s perception towards certain ethnic. In Indonesia, Chinese-Indonesian is the ethnic minority who often receive inequal representation in media, especially in online news site. This research aims to analyze representation of Chinese-Indonesian ethnic in three different online news media. The objective of the research is to compare the representation trend of Chinese-Indonesian in these three online news site during sensitive and neutral situation as well as the factors influencing the trend.